Atypical Pathogens Presenting With Pulmonary Consolidations Detected by Cell-Free DNA Next-Generation Sequencing in Patients With Hematologic Malignancies. Issue 2 (March 2022) - Caldararo, Mario; Algazaq, Jumanah; Schmidt, Elizabeth; Joanow, Alexa; Mariano, Amanda; Predmore, Jacqueline; Politikos, Ioannis; Cho, Christina; Stein, Eytan M.; Wen, Xiaoyun; Travis, William D.; Raible, Kevin; et al.
Abstract : Abstract: Identification of pathogens with pulmonary presentation in patients with hematologic malignancies may be challenging because of diagnostic difficulty related to the underlying malignancy and limitations of conventional microbiologic methods. Herein, we present a case series of 3 patients with pulmonary consolidations due to Legionella bozemanae necrotizing pneumonia, Pneumocystis jirovecii pneumonia, and disseminated Scedosporium infection, who were diagnosed by microbial cell-free DNA next-generation sequencing. We observed that this new sequencing modality was in agreement with criterion standard diagnostics, posing a potential solution to the problem of limited capability in diagnosing infections in hematological malignancy patients.